Rapid evidence profile #56: Examining types of misinformation and disinformation and the effectiveness of interventions to combat misinformation and disinformation - Velez, CM; Waddell, K; DeMaio, P; Bhuiya, AR; Lavis, JN; Wilson, MG (My University, 2023)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about types of misinformation and disinformation and the effectiveness of interventions to combat misinformation and disinformation in response to a decision-maker’s request.
Keywords: misinformation; disinformation; interventions; combat